2019
DOI: 10.3390/ijms20061433
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Background of Mice Influences the Effects of Cigarette Smoke on Onset and Severity of Experimental Autoimmune Encephalomyelitis

Abstract: Multiple sclerosis (MS) is the most common inflammatory disorder of the central nervous system (CNS) in young adults leading to severe disability. Besides genetic traits, environmental factors contribute to MS pathogenesis. Cigarette smoking increases the risk of MS in an HLA-dependent fashion, but the underlying mechanisms remain unknown. Here, we explored the effect of cigarette smoke exposure on spontaneous and induced models of experimental autoimmune encephalomyelitis (EAE) by evaluating clinical disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…The body weight of most affected mice began to stabilize and increase after 23 days post-immunization, paralleling a slight decrease in clinical scores by 0.5 or 1 before the scores stabilized. These fluctuations in EAE progression are in agreement with previous reports [104] , [20] , [23] , [78] . In addition, mice exposed to low and medium concentrations of CS showed a general tendency towards more severe disease symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The body weight of most affected mice began to stabilize and increase after 23 days post-immunization, paralleling a slight decrease in clinical scores by 0.5 or 1 before the scores stabilized. These fluctuations in EAE progression are in agreement with previous reports [104] , [20] , [23] , [78] . In addition, mice exposed to low and medium concentrations of CS showed a general tendency towards more severe disease symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Initial assessment of the brain sections by hematoxylin and eosin staining revealed a limited number of noticeable lesions in some sections, and the differences between the treatment groups were not observable (data not shown); thus, no further analyzes were conducted for the brain. This observation is in agreement with those from previous studies showing limited central nervous system (CNS) infiltrates and no evidence of brain lesions in MS mouse models [20] , [54] . We have also observed that EAE induction, which induces more severe clinical symptoms, does not necessarily induce brain pathology and primarily affects spinal cord pathology, particularly in the lumbar region (unpublished data).…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations